Ethosomes: A novel drug carrier. (October 2022) - Chauhan, Neha; Vasava, Parul; Khan, Sharuk L.; Siddiqui, Falak A.; Islam, Fahadul; Chopra, Hitesh; Emran, Talha Bin
Abstract: Ethosomal systems are newer lipid vesicular carriers that have been around for 20 years, but over that period they have grown significantly as a means of transdermal drug delivery. They have a sizable amount of ethanol in them. These nanocarriers carry medicinal substances with various physicochemical qualities throughout the skin and deep skin layers. Since they were created in 1996, ethosomes have undergone substantial investigation; new substances have been added to their original composition, creating new varieties of ethosomal systems. These innovative carriers, which can be added to gels, patches, and lotions, are prepared using several novel methods. In addition to clinical trials, many in vivo models are employed to assess the effectiveness of dermal/transdermal administration. This review focuses on different generation of ethosomes and their comparison with other conventional liposomes. Highlights: In early December 2019, a large pneumonia epidemic occurred in Wuhan, China. COVID-19 therapy focuses on treating the disease's symptoms. Globally, numerous studies and researchers have recently started fighting this virus. This paper examines the main characteristics of coronavirus and the computational analyses necessary to avoid infection.